54.2k views
1 vote
This one as well. Thanks! #22 a & b ​

This one as well. Thanks! #22 a & b ​-example-1
User Yathavan
by
5.5k points

2 Answers

5 votes

22a. Answer: y' = 90x + 33

Explanation:

y = 5u² + u - 1 u = 3x + 1

First take the derivative of y = 5u² + u - 1 with respect to u
\bigg((dy)/(du)\bigg)

y' = (2)(5u)(u') + (1)(u') - 0

= (10u)u' + u'

Next, take the derivative of u = 3x + 1 with respect to x
\bigg((du)/(dx)\bigg)

u' = 3 + 0

u' = 3

Now, input u = 3x + 1 and u' = 3 into the y' equation:

y' = (10u)u' + u'

= 10(3x + 1)(3) + 3

= 30(3x + 1) + 3

= 90x + 30 + 3

= 90x + 33

***********************************************************************

22b. Answer:
\bold{y'=-(4)/((2x+3)^(3))}

Explanation:


y=(1)/(u^2) u = 2x + 3


\text{We can rewrite y as }y=u^(-2)\\\text{Take the derivative of }y=u^(-2)\text{ with respect to u}\ \bigg((dy)/(du)\bigg)\\\\y'=(-2)(u^(-3))(u')

Next, take the derivative of u = 2x + 3 with respect to x
\bigg((du)/(dx)\bigg)

u' = 2 + 0

u' = 2

Now, input u = 2x + 3 and u' = 2 into the y' equation


y'=(-2)(2x+3)^(-3)(2)\\\\y'=-4(2x+3)^(-3)\\\\y'=-(4)/((2x+3)^(3))

User Ammar Abdullah
by
5.7k points
5 votes

Answer:

  • y' = 90x +33
  • y' = -4/(2x +3)^3

Explanation:

The chain rule says ...

dy/dx = (dy/du)·(du/dx)

For these problems that means ...

a. dy/dx = (10u +1)·(3) = 10((3x +1) +1)(3) = 3(30x +11)

dy/dx = 90x + 33

___

b. dy/dx = -2u^-3·(2)

dy/dx = -4/(2x +3)^3

User AMBasra
by
5.5k points